Sosialisasi Managemen Parkir Cerdas Pada Departemen Teknik Elektro Universitas Hasanuddin - Dewiani Dewi Djamaluddin; Syafruddin Syarif; Andani Achmad; Samuel Panggalo; Elyas Palantei; Wardi .; Zaenab .; Merna Baharuddin; Ejah Umraeni; Andini Dani Achmad; Azran Budi Arief; Milleneo .; Al Kautsar; Muh Anshar (Faculty of Engineering UNHAS, 2022)
The Department of Electrical Engineering, Faculty of Engineering, Hasanuddin University has an automatic gate based on Radio Frequency Identification (RFID) using employee and lecturer cards. However, it is still often found that vehicles are parked irregularly between the cars and motorbikes of employees and lecturers so that the parking space that should be able to accommodate more vehicles is limited. This service aims to implement a web-based parking reservation and monitoring system. Monitoring the availability of land and parking spaces is displayed in real-time on the website. In addition, users can make reservations on available land through the website online so there is no need to worry about the available parking space being used by other users. This system is placed in the parking lot of the Department of Electrical Engineering which consists of 20 parking slots that are installed in parallel and each slot area is equipped with sensors to indicate the presence of parked vehicles in the right place. Users can reserve a parking slot using a mobile phone that has been integrated with parking management. Parking slots that have been reserved by one user, cannot be used by other users. After the system is installed, demonstrations and socialization are carried out to students, lecturers, and staff of the Department of Electrical Engineering. With this parking access management system, the parking conditions are getting more regular and the security level is getting better because all vehicles that have access in and out are properly recorded.